Experimental study of distribution and quantitative characterization of discontinuous oil phase based on micro-CT - Yang, Jiangshan; Shan, Gaojun; Wang, Zhiqiang; Zhang, Qi; Yang, Yongfei; Ma, Wenjie (Frontiers in Earth Science, 2023)
When a sandstone reservoir enters the ultra-high water cut stage, the oil phase changes from continuous to discontinuous, which results in difficulties in the further development and utilization of the reservoir. It is important to clarify the flow law and distribution state of discontinuous oil phases to guide the remaining oil production. This study selected samples from sandstone reservoirs, accurately obtained oil and water phase information from digital core, and constructed matrix based on three-dimensional CT scanning to study the law of discontinuous oil phase distribution. We used digital cores to construct pore network models and calculate the pore radius, throat radius, pore-throat ratio, coordination number, and tortuosity to study the influence of pore structure on discontinuous oil phase flow law. A micro-displacement experiment consisting of two phases of simulated reservoir and development was designed. To improve the accuracy of the experiment, the related pressure was controlled to form bound water in the simulated reservoir formation stage. In the simulated reservoir development phase, in situ scanning of cores at different displacement stages was performed to obtain oil and water distributions at different stages in the same location. The number of oil droplets, 3D shape factor, Euler number, and saturation coefficient of the oil phase were calculated, and the micro-remaining oil clumps were quantitatively analyzed. According to the morphology and distribution characteristics, the remaining oil of the discontinuous phase was divided into the types of the throat, film, droplet, island, and corner. The results showed that the sample with a small pore-throat ratio, large coordination number, and small tortuosity was more likely to form dominant channels; moreover, the remaining oil was more concentrated in this state. In the remaining oil of the discontinuous phase, the number of droplets was the largest and had an obvious displacement effect. The island number was small because the selected samples had good connectivity and it is difficult to form large oil droplets in a single pore. In the ultra-high water cut stage, the throat number increased slowly, which was related to the formation of dominant channels. The corner and the film were difficult to displace; thus, their numbers increased steadily. The quantitative characterization of the discontinuous oil phase is helpful for further study of remaining oil at the pore scale.